Impact of intervention on adequate antenatal care and associated factors among Baiga tribal women of Madhya Pradesh: a case-control study - Kumar, Dinesh (International Journal Of Community Medicine And Public Health, 2024)
Background: This study was done to report on adequate antenatal care services owing to the impact of IEC intervention among deprived Baiga tribal women. Methods: Intervention study of 367 tribal women having a reproductive age of 15 to 49 year of 24 villages from district-Dindori. Pre-tested, administered intervention tools were implemented in intervention groups (12 villages) to enhance women’s knowledge for the use of ANC services (phase-I) and in phase-II impact evaluation survey of mother’s antenatal care utilization and related details were collected from mothers of both intervention and control group. Based on baseline indicators, a carry forward IEC-intervention study was taken considering the case-control design. Logistic regression analysis was used to identify the associated factors. Results: Use of ANC services 82.3% was found to have increased by 10.3% from baseline (72%); it was found significantly higher (88%) in the intervention group while lower (76.1%) in the control group. As regards 60% women received more than 3 ANC check-ups remarkably higher by 13% in the intervention group. Health institution child births 44.8% were found meaningfully improved by 36.8% from baseline (8%); also, it was revealed higher (49.7%) in the intervention group than lower (40%) in the control group. Women’s education and exposure of previous pregnancy has found strong association with adequate antenatal care in intervention groups. Conclusions: A comparatively high proportion of the use of ANC services and institutional child birth were found in the intervention group. Improving the access to more quality health services in other tribal communities may necessitate the intervention research.